2020
DOI: 10.1051/meca/2020015
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation into characterization and machining of Al + SiCp nano-composites using coated carbide tool

Abstract: The current research paper discusses the characterization and machining (turning) operation of aluminium (Al) and silicon carbide nano particle (SiCp) nano composite. The paper reveals proper distribution of silicon carbide nano particles (25nm) with aluminium metal matrix. Initially, tensile test has been carried on metal matrix nano composite to study its different properties. It was noticed that the properties of Al-SiCp increases by increasing the weight percentage of SiCp. Viker hardness test has also bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…It may also occur due to the application of diamond paste on samples before the EDS test. 32 From Figure 6, it is observed that hybrid Al-4032/SiC/GMP AMCs are abundant in Mg and Si.
Figure 5.SEM characterization of the base alloy and hybrid AMCs × 500.
Figure 6.EDS spectra of the base alloy and hybrid AMCs.
…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…It may also occur due to the application of diamond paste on samples before the EDS test. 32 From Figure 6, it is observed that hybrid Al-4032/SiC/GMP AMCs are abundant in Mg and Si.
Figure 5.SEM characterization of the base alloy and hybrid AMCs × 500.
Figure 6.EDS spectra of the base alloy and hybrid AMCs.
…”
Section: Resultsmentioning
confidence: 97%
“…It may also occur due to the application of diamond paste on samples before the EDS test. 32 From Figure 6, it is observed that hybrid Al-4032/ SiC/GMP AMCs are abundant in Mg and Si.…”
Section: Morphological Analysismentioning
confidence: 97%
See 1 more Smart Citation
“…The model is significant only when its P-value is lower than 0.05. ANOVA for both flank wear and surface roughness are presented in Table 5 [37,38]. Flank wear MLR model is found to be significant whereas surface roughness MLR model is insignificant as their P-value exceeds 0.05.…”
Section: Surface Roughness ðRaþ ¼mentioning
confidence: 98%
“…The result revealed that machining parameters were significantly affected the machining performance. Swain et al [21] used coated carbide tool for machining of Al-MMC based nano composite. Machining parameters were optimized using principal Component analysis.…”
Section: Introductionmentioning
confidence: 99%